2012
DOI: 10.1111/j.1745-9125.2012.00280.x
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Other People's Children: Racialized Views of Delinquency and Whites’ Punitive Attitudes Toward Juvenile Offenders*

Abstract: The juvenile justice system was founded on, and until recently developed around, the idea that society should afford delinquents more leniency and rehabilitative care than adult criminals because of their lower levels of physical and cognitive development and, thus, diminished culpability for law violations and higher amenability to treatment. The past four decades, however, have witnessed a sustained movement to recriminalize delinquency through the enactment of policies that treat juvenile offenders more lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
107
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(116 citation statements)
references
References 86 publications
5
107
1
3
Order By: Relevance
“…In response to calls for more nuanced, theoretically informed analyses of views toward juvenile justice and, more generally, punishment (see, e.g., Jonson et al 2013;Mears et al 2007;Pickett and Baker 2014;Pickett and Chiricos 2012), this paper drew on several lines of scholarship to argue that opinion about core philosophical tenets or dimensions of the juvenile court may influence support for balanced justice, itself an approach to sanctioning that comports with the ideals envisioned by the court's founders. Briefly, the analyses indicated that these views influence support for balanced justice.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…In response to calls for more nuanced, theoretically informed analyses of views toward juvenile justice and, more generally, punishment (see, e.g., Jonson et al 2013;Mears et al 2007;Pickett and Baker 2014;Pickett and Chiricos 2012), this paper drew on several lines of scholarship to argue that opinion about core philosophical tenets or dimensions of the juvenile court may influence support for balanced justice, itself an approach to sanctioning that comports with the ideals envisioned by the court's founders. Briefly, the analyses indicated that these views influence support for balanced justice.…”
Section: Resultsmentioning
confidence: 98%
“…In addition, some scholars have drawn on such theories as racial threat and focal concerns (Leiber and Mack 2003;Steffensmeier et al 1998) to understand which individuals or social groups support punitive sanctioning. Pickett and Chiricos (2012), for example, have argued that individuals who are more likely to typify youth crime as a predominantly ''black'' phenomenon are more likely to support punitive measures (see, generally, Feld 1999; Ward 2012). Other theories (e.g., Applegate et al 2000;Jacobs and Carmichael 2004;Taylor et al 1979), along with studies focused on juvenile offenders (e.g., Garland et al 2012;Mears 2001;Triplett 1996), have suggested that support for tougher punishment may be greater among whites and political or religious conservatives.…”
Section: Theoretical Accounts Of Public Opinion About Sanctioning Youthmentioning
confidence: 97%
See 1 more Smart Citation
“…The analysis includes three dependent variables to gauge the racial typification of crime. Consistent to prior research (Drakulich ; Pickett and Chiricos ; Unnever and Cullen ), we utilize relative measures to capture the perceived percentage of violent, property, and drug crimes committed by African Americans in relation to the perceived percentage of these crimes committed by whites. Typification of Criminals as African Americans was measured by asking respondents, “Out of every 100 people who commit [a violent crime/a property crime/sell illegal drugs] in this country, what number do you think are white, black, Latino, or some other race/ethnicity?” The three outcomes (violence, property, and selling illegal drugs) were calculated by subtracting the responses about whites from the responses about blacks (e.g., percentage committed by blacks minus percentage committed by whites) for each typology of crime, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…En efecto, son abundantes los estudios que, empleando técnicas diferentes, han encontrado una relación positiva entre la ideología conservadora y los posicionamientos de carácter punitivo (Applegate y Davis, 2006;Mancini et al, 2009;Miller y Applegate, 2015;Picket y Chiricos, 2012;Roberts y Indermaur, 2007;Turner et al, 1997).…”
Section: Los Factores Explicativos Y Sus Implicaciones Teóricas Para unclassified